1994
DOI: 10.3109/02813439409003703
|View full text |Cite
|
Sign up to set email alerts
|

Fructosamine cannot replace HbAlc in the management of type 2 diabetes (NIDDM)

Abstract: Our study indicates that fructosamine and fasting capillary blood glucose are poor indicators of the level of HbA1c in NIDDM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Another study 158 reported a good correlation between FPG, fructosamine and GHb. However, further studies suggested that fructosamine was not a good predictor of GHb 159,160 or self-monitored blood glucose levels. 161 Although fructosamine levels generally correlate well with HbA 1c within a population, the value of HbA 1c in an individual cannot be inferred with any reliability from the level of fructosamine.…”
Section: Validity Of Fructosamine Testing As An Indicator Of Glycaemic Controlmentioning
confidence: 93%
See 1 more Smart Citation
“…Another study 158 reported a good correlation between FPG, fructosamine and GHb. However, further studies suggested that fructosamine was not a good predictor of GHb 159,160 or self-monitored blood glucose levels. 161 Although fructosamine levels generally correlate well with HbA 1c within a population, the value of HbA 1c in an individual cannot be inferred with any reliability from the level of fructosamine.…”
Section: Validity Of Fructosamine Testing As An Indicator Of Glycaemic Controlmentioning
confidence: 93%
“…166 In contrast, GHb correlated well with capillary blood glucose measurements in both patients with normal renal function and those with renal failure. 166 A further study 159 found weak correlations between fructosamine, HbA 1c and blood glucose in type 2 DM elderly patients, and suggested that the presence of other chronic conditions, such as liver cirrhosis and nephrotic syndrome, 61 could also influence fructosamine levels.…”
Section: Standardisation Of Fructosamine Testingmentioning
confidence: 97%
“…The most commonly used test for GSP is the fructosamine assay which has advantages over the HbA 1c assay in being more convenient, faster and cheaper to carry out, advantages that may make the test particularly useful where resources are limited 36, 37. The relationship between this variable and other measures of blood glucose levels and its potential use in clinical practice have yet to be established 38–42. The results of some studies, however, have indicated that the fructosamine test may be a useful alternative to HbA 1c in some populations.…”
Section: Setting and Assessing Goalsmentioning
confidence: 99%